Reexamination of human T cell lymphotropic virus (HTLV-I/II) prevalence - Zucker-Franklin, Dorothea (The National Academy of Sciences of the USA, 1997)
In the United States, blood donors are being screened for infection with human T cell lymphotropic viruses I and II (HTLV-I/II) by serologic means, which detect antibodies to the structural proteins of these viruses. Because patients with mycosis fungoides (MF) usually do not have such antibodies even though their cells harbor HTLV-I Tax and/or pol proviral sequences, it was questioned whether the prevalence of HTLV infection among healthy blood donors may also be underestimated by current means of testing. To examine this possibility, a study on specimens of relatives of mycosis fungoides patients (MFR) was begun. In addition, to collect data more expeditiously, a cohort of former injection drug users (IDUs) was tested by routine serologic methods, as well as by PCR/Southern blot analysis for Tax, pol, and gag proviral sequences and Western blot analysis for antibodies to the Tax gene product. To date, 6/8 MFRs and 42/81 (51.8%) of HIV-negative IDUs proved to be positive for HTLV, whereas routine serology identified none of the MFR and only 18/81 (22.2%) of the IDUs. Among the latter test subjects, the incidence of HTLV-I also proved to be 10 times higher than expected. Therefore, it is likely that among healthy blood donors infection with HTLV-I/II is more prevalent than is currently assumed. Since Tax is the transforming sequence of HTLV-I/II, testing for Tax sequences and antibodies to its gene product may be desirable in blood transfusion and tissue donor facilities.